Exploring the Selectivity Profile of Sigma Receptor Ligands by Molecular Docking and Pharmacophore Analyses - Righetti, Giada; Tonelli, Michele; Fossa, Paola; Cichero, Elena (Medicinal Chemistry, 2021)
Background: Sigma receptors (σRs), initially classified as an additional class of opioid receptors, are now recognized as a unique entity with no homology to opioid receptors divided into two distinct subtypes, namely σ1R and σ2R. σ1R-targeting ligands have been conceived and explored for the treatment of various neurodegenerative disorders and neuropathic pain. Activation of the σ2R appears to be involved in the regulation of cellular proliferation and cell death. Objective: Up to now, the rational design of novel σ1R ligands was efficiently guided by computational methods, especially relying on homology modeling studies. Conversely, the limited number of in silico studies was applied in the search of σ2R-targeting compounds. Herein we explored several series of σ1R ligands, by computational methods, featuring variable selectivity profile towards σ1R and σ2R in order to gain useful information guiding the rational design of more selective ligands. Methods: Based on the recent X-ray crystallographic structure of the human σ1R, in-depth molecular docking studies on different series of σR ligands have been performed. These calculations have been followed by molecular dynamic simulations (MD) and two pharmacophore analyses, taking into account the activity levels towards σ1R and σ2R. Results: Structure-based studies revealed key contacts to be achieved in order to guide selectivity of σ1R-targeting compounds while the two pharmacophore models described the main features turning into effective σ1R or σ2R ligands. Conclusion: The applied computational approach allowed a more comprehensive exploration of the structure-activity relationship (SAR) within the herein analyzed σR ligands, deriving useful guidelines for the rational design of more selective compounds.
Keywords: modeling